Protective Effect of the Fruit Hull of Gleditsia sinensis on LPS-Induced Acute Lung Injury Is Associated with Nrf2 Activation. (29th January 2012) - Choi, Jun-Young; Kwun, Min Jung; Kim, Kyun Ha; Lyu, Ji Hyo; Han, Chang Woo; Jeong, Han-Sol; Ha, Ki-Tae; Jung, Hee-Jae; Lee, Beom-Joon; Sadikot, Ruxana T.; Christman, John W.; Jung, Sung-Ki; et al.
Abstract : The fruit hull of Gleditsia sinensis (FGS) has been prescribed as a traditional eastern Asian medicinal remedy for the treatment of various respiratory diseases, but the efficacy and underlying mechanisms remain poorly characterized. Here, we explored a potential usage of FGS for the treatment of acute lung injury (ALI), a highly fatal inflammatory lung disease that urgently needs effective therapeutics, and investigated a mechanism for the anti-inflammatory activity of FGS. Pretreatment of C57BL/6 mice with FGS significantly attenuated LPS-induced neutrophilic lung inflammation compared to sham-treated, inflamed mice. Reporter assays, semiquantitative RT-PCR, and Western blot analyses show that while not affecting NF- κ B, FGS activated Nrf2 and expressed Nrf2-regulated genes including GCLC, NQO-1, and HO-1 in RAW 264.7 cells. Furthermore, pretreatment of mice with FGS enhanced the expression of GCLC and HO-1 but suppressed that of proinflammatory cytokines in including TNF- α and IL-1 β in the inflamed lungs. These results suggest that FGS effectively suppresses neutrophilic lung inflammation, which can be associated with, at least in part, FGS-activating anti-inflammatory factor Nrf2. Our results suggest that FGS can be developed as a therapeutic option for the treatment of ALI.